La mejor Navidad de Froggy - London, Jonathan, 1947-; Remkiewicz, Frank; Fabiancic, Miriam (New York : Scholastic, 2002)
Froggy experiences his first Christmas, celebrating it with his friends and family.
"Originally published in English as Froggy's best Christmas" T.p. verso.
Keywords: Frogs -- Juvenile fiction; Christmas fiction; Spanish language materials; Fiction